Detecting plagiarism in a student's assignment based on web pages referenced by a student - Ezra Anandaraj, Esther Sangeedha; Mering, Helena Ping (University Malaysia Sarawak, (UNIMAS), 2004)
Students in institutions of higher learning refer to many sources of information to complete assignments. More often than not, these sources are copied directly or paraphrased without proper citation. This is considered plagiarism.